2011
DOI: 10.1104/pp.110.169706
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Seed Germination in the Close Arabidopsis RelativeLepidium sativum: A Global Tissue-Specific Transcript Analysis      

Abstract: The completion of germination in Lepidium sativum and other endospermic seeds (e.g. Arabidopsis [Arabidopsis thaliana]) is regulated by two opposing forces, the growth potential of the radicle (RAD) and the resistance to this growth from the micropylar endosperm cap (CAP) surrounding it. We show by puncture force measurement that the CAP progressively weakens during germination, and we have conducted a time-course transcript analysis of RAD and CAP tissues throughout this process. We have also used specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 118 publications
(169 reference statements)
5
59
0
2
Order By: Relevance
“…Transcripts involved in cell wall modifications were found to be more abundant in the translatome of nondormant seeds than dormant seeds. Overrepresentation of cell wall-related transcripts in the transcriptome was shown in Lepidium sativum (Morris et al, 2011) and Arabidopsis (Endo et al, 2012) germinating seeds and in the translatome of sunflower seeds (Layat et al, 2014). Transcripts for expansins such as EXPA1, EXPA10, EXPA4, and EXPA2 (At1g69530, At1g26770, At2g39700, and At5g05290; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts involved in cell wall modifications were found to be more abundant in the translatome of nondormant seeds than dormant seeds. Overrepresentation of cell wall-related transcripts in the transcriptome was shown in Lepidium sativum (Morris et al, 2011) and Arabidopsis (Endo et al, 2012) germinating seeds and in the translatome of sunflower seeds (Layat et al, 2014). Transcripts for expansins such as EXPA1, EXPA10, EXPA4, and EXPA2 (At1g69530, At1g26770, At2g39700, and At5g05290; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The testa is dead tissue, but cell wall-modifying enzymes could be secreted from the underlying endosperm to cause modifications in the inner testa cell walls, which could lead to sitespecific weakening. A number of cell wall-modifying genes, and the enzyme activities of their products, have been shown to be differentially regulated before ER in the seeds of various endospermic species, such as b-1,3-glucanase in tobacco (Nicotiana tabacum; Leubner-Metzger et al, 1995;Manz et al, 2005), b-1,4-mannanase in tomato (Solanum lycopersicum; Nonogaki et al, 2000), garden cress (Morris et al, 2011), and Arabidopsis (Iglesias-Fernández et al, 2011), and xyloglucan endotransglycosylases/hydrolases in garden cress (Voegele et al, 2011;Graeber et al, 2014) and Arabidopsis (Endo et al, 2012), and species-specific changes in cell wall composition have been observed during the later germination process (Lee et al, 2012), supporting the importance of the cell wall remodeling during seed germination.…”
Section: Discussion Tr Constitutes a Transition Between Phases Of Genmentioning
confidence: 99%
“…After TR, endosperm resistance decreases through tissue softening, a process called endosperm weakening (Müller et al, 2006;Linkies et al, 2009). Both radicle elongation and endosperm weakening require cell wall modifications (Schopfer, 2006;Müller et al, 2009;Morris et al, 2011).…”
mentioning
confidence: 99%
“…Radicle protrusion through the micropylar endosperm is also stimulated by ethylene, which has an antagonist action with ABA on endosperm cap weakening (Linkies and LeubnerMetzger, 2012). Microarray analyses highlighted the importance of cell wall remodeling processes during germination in various species (Penfield et al, 2006;Morris et al, 2011;Endo et al, 2012;Martínez-Andújar et al, 2012;Dekkers et al, 2013). These studies provided compelling evidence that the tissue-specific expression of genes encoding cell wall biosynthesis or modification enzymes, and their differential response to hormonal signals in the endosperm and embryo, influences the rate of germination.…”
mentioning
confidence: 99%